Does initial vocational training foster innovativeness at the company level? Evidence from German establishment data - Matthies, Eike [Verfasser]; Haverkamp, Katarzyna [Verfasser]; Thomä, Jörg [Verfasser]; Bizer, Kilian [Verfasser] (My University, 2024)
"The potential role of vocational education and training (VET) for innovation is the subject of a growing number of studies. Quantitative evidence for this relationship, however, remains scarce. Therefore, this paper uses representative German company data to examine the relationship between a firm’s initial VET activity and its innovation output. The results based on linear probability models and entropy balancing indicate that the direct link between initial VET and firm-level innovation is more ambiguous than often postulated. For the total population of German companies, a positive correlation with initial VET is only found for incremental product and process innovations. Furthermore, a significant link between initial VET and innovation is only found in the group of microenterprises with less than 10 employees. From this, we conclude that participation in the VET system primarily promotes the innovative capacity of very small training companies through the diffusion of new technologies and knowledge. The paper concludes with implications for policy and research." (authors' abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.2 Unternehmen und Behörden; 370; Berufsausbildung; Innovationsforschung; Innovation; Betrieb; Ausbildungsverhalten; Einflussfaktor